Answer: [tex]-x^2+8x+6[/tex]
Step-by-step explanation:
For this exercise is important to remember the multiplication of signs:
[tex](+)(+)=+\\(-)(-)=+\\(-)(+)=-[/tex]
Then, Given the following expression:
[tex]2x^2+7x+6 - (3x^2-x)[/tex]
The first step is to distribute the negative sign in order to eliminate the parentheses:
[tex]2x^2+7x+6 - (3x^2-x)=2x^2+7x+6 -3x^2+x[/tex]
The final step is to add the like terms.
Therefore, the polynomial that represents the differences is:
[tex]=-x^2+8x+6[/tex]